A Text Mining Algorithm Optimising the Determination of Relevant Studies - Khashfeh M.; Mahmoud M.A.; Ahmad M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Abstracting; Autonomous agents; Computational methods; Multi agent systems; Robotics; Agent-based model; Document languages; Length determination; Literature studies; Preparation process; Regular expressions; Relevant Studies; Text mining; Data mining